SATIRICAL WORKS IN ENGLISH LITERATURE: JONATHAN SWIFT AND OTHER SATIRICAL WRITERS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This thesis explores the role of satire in English literature, with a particular focus on Jonathan Swift and other prominent satirical writers. It examines how satire has been used as a tool for social and political critique, analyzing key works by Swift, such as “Gulliver's travels” and “A Modest Proposal”, alongside contributions from other significant satirists. The study aims to understand the techniques of satire employed, the historical and cultural contexts of the works, and the impact of satire on both contemporary and modern audiences.